Perbaikan Mutu dan Penyusunan Instruksi Kerja pada Pembuatan Keripik Sanjai Balado Nina di Bukittinggi - Tjahja Muhandri; Olivia Rezki (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Sanjai balado Nina chips industry in Bukittinggi had some weakness on it’s product quality. The color of balado spice tended to be dark and easily faded during storage. The purpose of this extension activity was to increase the quality product by improving the formula and its production process. The major cause of lowering the quality of its product was identified by Ishikawa Diagram. The best results were analyzed using sensory test (rating hedonic test). Sensory evaluation of the 70 consumers showed that consumers mostly like the formula using 100 g of red chilli, 60 g of glucose syrup, 40 g of sugar, and 5 g of salt.